PENGENALAN STABILISASI DAN PEMADATAN TANAH DI DESA PASIR LOR KECAMATAN KARANGLEWAS KABUPATEN BANYUMAS (Universitas Wijayakusuma Purwokerto, 2024)
Development programs in all fields, which are being intensively carried out in Banyumas Regency, include the construction of transportation, buildings, bridges and so on. In the transportation sector, namely the construction of roads at several points in the Banyumas area. Pasir Lor Village is one of the villages in the Karanglewas, Banyumas. Regarding road construction, especially in this area, the author would like to explain about soil material as a support for road construction, namely